A method for preparing tantalum carbide coating by CVD and its products

By reacting at high temperature in a mixed gas stream between hydrogen and alkanes, using tantalum alkoxide as a precursor, tantalum carbide coatings are prepared by chemical vapor deposition method, which solves the poor ductility, fragility and high processing costs of existing tantalum carbide coating products. Problem, high purity, corrosion and wear resistance coating products are achieved, and production costs are reduced.

CN115786876BActive Publication Date: 2025-02-07XIAMEN SINOMA HANGTE TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211248282.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-12
Publication Date
2025-02-07
Estimated Expiration
2042-10-12

AI Technical Summary

Technical Problem

The existing tantalum carbide coating products have problems such as poor ductility, fragility, and high processing costs. In addition, chemical vapor deposition methods are prone to cracks during the deposition process, which reduces the protectiveness of the coating and has dangerous by-products.

Method used

Tantalum salt is used as the precursor to react at high temperature in a mixed gas stream of hydrogen and alkanes, and a high-purity tantalum carbide coating is prepared on the substrate surface by chemical vapor deposition method, and the process parameters are optimized to reduce the deposition temperature and production costs.

Benefits of technology

It realizes high purity, corrosion resistance, wear resistance and good appearance quality tantalum carbide coating products, reduces production costs and improves the protection and adhesion of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115786876B_ABST
    Figure CN115786876B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a tantalum carbide coating by using CVD, wherein a tantalum carbide coating is formed on a substrate surface by chemical vapor deposition using tantalum alkoxide, alkane and hydrogen. The present invention can effectively enable the substrate to obtain excellent high temperature resistance, corrosion resistance and friction resistance, and at the same time has the effect of effectively controlling the overflow of impurity components in the substrate, improving the surface finish and the aesthetics of the product, and realizes large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic materials, and in particular relates to a method for preparing a tantalum carbide coating by utilizing CVD and a product thereof. Background Art

[0002] Tantalum carbide is a superconducting ceramic material with a golden appearance. It has the advantages of high hardness (2100 HV 0.05), high melting point (3880°C), corrosion resistance, and low adhesion. It has become an emerging ceramic material in recent years. Powdered tantalum carbide is widely used in the smelting of specialty alloys. Tantalum carbide ceramics have broad application prospects in the semiconductor, chemical, metallurgical, mold processing, aerospace, and nuclear industries. They are excellent barrier, shielding, and wear-resistant materials. However, their widespread use is restricted by poor ductility, fragility, and high processing costs.

[0003] The main preparation methods of tantalum carbide include carbon thermal reduction method, compound method, high temperature molten salt method, chemical vapor deposition method and sol-gel method. The carbon thermal reduction method is to mix tantalum oxide with carbon at high temperature for primary and secondary carbonization to produce tantalum carbide. This method has a high reduction temperature and a slow reaction rate, and can only produce tantalum carbide in block or large granular form. The compound method is a common solid-phase preparation process. Under certain conditions, tantalum and carbon directly react chemically to produce tantalum carbide. The high temperature molten salt method is more used to improve the performance of carbon fibers. The sol-gel method is to use organic tantalum or tantalum inorganic salt as a precursor, react with a solvent to form a sol, and then apply it on the substrate. After gelation, drying and sintering, a tantalum carbide coating is obtained. This method has a long cycle and a thin coating, poor bonding with the substrate, and is prone to cracks.

[0004] Chemical Vapor Deposition (CVD) is a process that uses gaseous substances to produce chemical reactions and transport reactions on solids, thereby producing solid deposits. This technology is not only used in coatings of heat-resistant materials, but also in the preparation of fiber-reinforced composites and the refining of high-purity metals. It is an advanced technology with a wide range of applications and is suitable for the preparation of coatings for workpieces with complex shapes or large areas. CVD can produce tantalum carbide coatings with higher crystallinity and density. However, due to the way chemical vapor deposition grows along the same crystal direction, cracks in the material can easily break along the crystal direction to the substrate surface, reducing the protectiveness of the coating. In addition, the use of CVD to prepare tantalum carbide coatings produces hydrochloric acid as a byproduct, which is dangerous. Summary of the Invention

[0005] The present invention addresses the shortcomings of existing tantalum carbide coated products. Tantalum alkoxide is used as a precursor, reacts at high temperature in a mixed gas flow of hydrogen and alkanes, and a high-purity tantalum carbide coating material is prepared on the surface of a substrate by chemical vapor deposition. This effectively solves the drawbacks of existing tantalum carbide coated products, provides a method for preparing tantalum carbide coated products that are corrosion-resistant, wear-resistant, have good appearance quality, and are not prone to adhesion, and reduces production costs.

[0006] To achieve the above objectives, the present invention provides a method for preparing a tantalum carbide coating using CVD. Tantalum alkoxide is used as a precursor, which is then vaporized and subjected to a reduction reaction with an alkane and hydrogen in a chemical vapor deposition device. The resulting coating is then deposited on the surface of a blank to form the desired tantalum carbide coating. Preferably, the tantalum alkoxide is at least one of tantalum methoxide or tantalum ethoxide. Preferably, the alkane is at least one of methane, ethane, and propane. The method specifically comprises the following steps:

[0007] ① Heating step: placing the substrate in a CVD reaction chamber, evacuating the reaction chamber, and heating under inert gas protection at a temperature of 400-500°C;

[0008] ② Deposition step: After the heating step, a mixture of tantalum alkoxide gas, hydrogen, and alkane gas is introduced into the reaction chamber at a pressure of 15,000 Pa to 20,000 Pa and a temperature of 400 to 500° C. to deposit a tantalum carbide coating on the surface of the substrate;

[0009] ③ a cooling step, after the deposition step, cooling the tantalum carbide coated product to room temperature;

[0010] ④ Cleaning step: After cooling to room temperature, take out the product and clean it with ethanol.

[0011] Furthermore, the vaporization temperature of the tantalum alkoxide is 200-300°C.

[0012] Furthermore, the reaction chamber is a stainless steel reaction chamber.

[0013] Furthermore, the volume ratio of the tantalum alkoxide gas to the alkane is 1:1-2, and the volume ratio of the tantalum alkoxide gas to the hydrogen is 1:1-3.

[0014] Furthermore, the flow rate of the tantalum alkoxide gas is 2-6 SLM, the flow rate of the alkane gas is 2-12 SLM, and the flow rate of the hydrogen gas is 2-18 SLM.

[0015] Preferably, the heating step further includes pretreatment of the substrate: cleaning the surface of the substrate to be deposited with distilled water to remove dirt, and then drying it at 150° C. to 200° C. for 8 to 15 hours until it is completely dried.

[0016] A product with a tantalum carbide coating comprises a substrate and a tantalum carbide coating formed on the surface of the substrate, with a thickness of 15 to 300 microns. The substrate includes a metal substrate, a carbon material substrate, a ceramic substrate, and a quartz substrate.

[0017] After adopting the above scheme, the beneficial effects achieved are:

[0018] (1) The deposition temperature of the present invention is low, the reaction product gas is non-corrosive or non-toxic, the equipment requirements are low, the entire production process is safe and reliable, more environmentally friendly, and suitable for large-scale industrial production.

[0019] (2) The tantalum carbide coating produced by this method is of high purity and free of impurities.

[0020] (3) The tantalum carbide coating prepared by the present invention effectively isolates the substrate from the external environment and can effectively protect the substrate.

[0021] (4) A corrosion-resistant and wear-resistant tantalum carbide isolation coating is prepared on the surface of the substrate by chemical vapor deposition, and the thickness of the coating is 15~300 microns.

[0022] (5) The present invention has relatively loose requirements on the substrate and can be deposited on various irregular surfaces with good uniformity and dense structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram of the chemical vapor deposition system structure used in the present invention;

[0024] Figure 2 This is a cross-sectional view of the tantalum carbide coating of Example 1;

[0025] Figure 3 This is a cross-sectional view of the tantalum carbide coating of Example 2;

[0026] Figure 4 This is a cross-sectional view of the tantalum carbide coating of Example 2 (unpolished);

[0027] Figure 5 This is the surface morphology of the tantalum carbide coating of Example 1;

[0028] Figure 6 This is the surface morphology of the tantalum carbide coating of Example 2;

[0029] Figure 7 This is a metallographic photograph of the tantalum carbide coating in Example 1. DETAILED DESCRIPTION

[0030] Tantalum carbide is generally difficult to machine due to its high melting point, high hardness, and poor ductility. The commonly used hot pressing and sintering methods are also difficult to achieve dense, porosity-free finishes. Therefore, the use of chemical vapor deposition (CVD) to produce tantalum carbide-coated products holds great significance and broad application prospects.

[0031] CVD refers to a high-temperature gas-phase reaction, such as the thermal decomposition of metal halides and organometallic compounds, reduction, or chemical reaction of their mixed gases at high temperatures to precipitate inorganic materials such as metals, oxides, and carbides. This technology is not only used in the coating of heat-resistant materials, but also in the preparation of fiber-reinforced composites and the refining of high-purity metals. It is an advanced technology with a wide range of applications. Chemical vapor deposition technology is a process that uses gaseous substances to produce chemical reactions and transport reactions on solids, thereby producing solid deposits.

[0032] Tantalum carbide deposition using tantalum alkoxides as precursors offers advantages over other inorganic or organic tantalum compounds, such as low melting and boiling points, improved cost-effectiveness, high purity, and safe availability. As alkoxides, tantalum alkoxides are simpler to prepare and more readily available than other organic compounds. Their lower melting and boiling points also facilitate their vaporization, facilitating the deposition process.

[0033] Table 1 Physical and chemical properties of tantalum alkoxides used in deposition

[0034] Tantalum alkoxide Melting point (℃) Boiling point (℃) <![CDATA[Tantalum methoxide C5H 15 O5Ta]]> 50 189℃(10 torr) <![CDATA[Tantalum(V) ethoxide C 10 H 25 O5Ta]]> 21 155

[0035] Chemical vapor deposition is a complex process that involves thermodynamics and kinetics of chemical reactions, as well as heat and mass transfer. On the one hand, the chemical reaction must be controlled within the reaction chamber, while on the other hand, the product must form nuclei and grow on the surface of the blank. While chemical reactions between chemical substances are possible, there's no guarantee that the reaction will occur efficiently. Numerous trials have been conducted to continuously optimize process parameters.

[0036] The chemical reaction equation of tantalum ethoxide with methane and hydrogen is as follows:

[0037] 2C 10 H 25 O5Ta+2CH4+H2——2TaC+10C2H5OH

[0038] Compared to other tantalum compounds, tantalum methoxide or tantalum ethoxide has lower melting and boiling points, is more easily vaporized into gas, and has higher reactivity, making it an excellent raw material for CVD preparation of tantalum carbide coatings. Tantalum methoxide or tantalum ethoxide is also generally higher in purity. Compared to other inorganic tantalum compounds, tantalum methoxide or tantalum ethoxide chemical vapor deposition reaction temperatures are low, and the tail gas products do not contain HF or HCl, are non-corrosive, have low equipment requirements, and are easy to maintain. The entire production process is safe, reliable, environmentally friendly, non-toxic, and more in line with current green environmental protection concepts.

[0039] A method for preparing a tantalum carbide coating by CVD, comprising the following steps:

[0040] (1) Flushing and evacuating the vapor deposition equipment and all pipelines with inert gas;

[0041] (2) Clean and decontaminate the blank to be deposited, dry it, and place it in the reaction chamber;

[0042] (3) Exhausting non-reactive gases and impurities that enter the vapor deposition equipment during the placement of the green body;

[0043] (4) After checking that the vapor deposition equipment is sealed properly, control the vacuum degree in the vapor deposition equipment to 15000~20000Pa through a vacuum pump, and heat the temperature in the reaction chamber to 400~500℃;

[0044] (5) placing tantalum alkoxide in a vaporization chamber and heating it to 200-300° C. to vaporize it, and introducing the vaporized tantalum alkoxide gas into a mixing tank at a tantalum alkoxide gas flow rate of 2-6 SLM. At the same time, introducing alkane and hydrogen into the mixing tank at a hydrogen flow rate of 2-18 SLM and an alkane flow rate of 2-12 SLM. After being fully mixed in the mixing tank, the mixture is introduced into a reaction chamber to perform a chemical vapor deposition reaction on the blank. After a certain reaction time, a tantalum carbide coating of 15-300 μm is formed on the surface of the substrate.

[0045] (6) Disconnect the heating power supply, stop heating, and allow the reaction chamber to cool down naturally; when the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coating material.

[0046] Among them, the chemical vapor deposition equipment includes a vaporization chamber and a reaction chamber. Figure 1As shown, the chemical vapor deposition apparatus 1 comprises a reaction chamber 11, within which a workpiece 12 (e.g., a blank) to be deposited is placed. The reaction chamber 11 is provided with two vents, one connected to an air inlet pipe 13 and the other to a vacuum pipe 14. The reaction chamber 11 is also equipped with a heating device (not shown) for heating the reaction chamber. The outer end of the vacuum pipe 14 is connected to a vacuum pump 17. The air inlet pipe 13 is connected to a mixing tank 16, which is connected to at least one vent pipe 161. In this embodiment, two vent pipes 161 are provided, through which reducing gas and inert argon gas are introduced, respectively. The mixing tank 16 is connected to a vaporization chamber 15, which heats and vaporizes tantalum ethoxide. The vaporized tantalum ethoxide gas enters the mixing tank 16 and is thoroughly mixed with other gases. The flow rate of the reaction gases is regulated by a gas control device 18.

[0047] Tantalum alkoxide is vaporized in a vaporization chamber using heat energy, turning it into a gaseous state. The gaseous reactants react in the reaction chamber, converting the vapor into a tantalum deposit.

[0048] The vapor deposition reaction chamber uses a stainless steel reaction chamber, which can ensure long-term stable operation and is the best choice.

[0049] The purpose of steps (1) to (3) is to increase the bonding strength between the coating or composite material and the blank, and to perform pretreatment before chemical vapor deposition. Other inert gases that do not chemically react with the reactants can be selected, such as argon or neon, or a mixture of argon and neon.

[0050] In step (4), the reaction chamber temperature needs to ensure that the mixed gas of tantalum alkoxide, alkane and hydrogen can fully react, but the reaction chamber temperature should not be too high, otherwise the chemical deposition reaction will occur prematurely in other places before contacting the blank.

[0051] The alkane gas used in the present invention can be a lower alkane having 1-3 carbon atoms, namely methane, ethane, propane or a mixture thereof, preferably methane. Tantalum carbide is prepared using methane and tantalum methanol or tantalum ethanol gas. Compared with other hydrocarbons, the biggest advantage of methane gas is that it produces fewer by-products and is safe. During the preparation process, the reaction temperature, vacuum degree, reaction gas flow rate and ratio have a major impact on the speed of the deposition reaction and the structure and properties of the deposited layer. The ratio of methane gas to tantalum alkoxide gas and hydrogen gas affects the concentration of the reactants. Too low or too high a reactant concentration affects the deposition efficiency. The reaction gas must have sufficient residence time on the surface of the blank to participate in the reaction. The deposition rate is controlled by the adsorption and desorption processes occurring between the reaction gas and the blank surface. When the gas flow rate increases, the source material participating in the reaction per unit time increases, which is conducive to the reaction proceeding in the direction of the product and the deposition rate increases. However, when the gas flow rate exceeds a certain range, some gas will not participate in the reaction and directly pass through the blank surface, resulting in waste. The process parameters in the chemical vapor deposition preparation process, such as the reaction chamber temperature, equipment vacuum, reaction gas flow and ratio, tantalum alkoxide vaporization temperature, deposition time and heat treatment process, all have an impact on the material properties of the product. They are mutually restrictive and complementary, and must be analyzed and adjusted uniformly when making process adjustments.

[0052] Preferably, tantalum alkoxide gas, alkane and hydrogen are fully mixed in a gas mixing tank and then introduced into a reaction chamber for chemical vapor deposition reaction. Mixed gas intake can make deposition more uniform without excessive deposition or under-deposition.

[0053] In order to further explain the technical solution of the present invention, the present invention is described in detail below through specific examples. In industrial production, considering the economic cost, argon is used as an inert gas for protection in the embodiments, and it can also be extended to other inert gases that do not participate in the chemical reaction. The following examples will help researchers in this field to further understand the present invention, but do not limit the present invention in any form. It should be pointed out that for those of ordinary skill in the art, several adjustments and improvements can also be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0054] The following test equipment uses general equipment unless otherwise specified, which does not affect the determination of the final results; the electron microscope is Thermo Fisher Apero2, the elemental analyzer is Thermo Fisher Flash 2000, and the ICP is Shimadzu ICPE-9000.

[0055] Example 1

[0056] The chemical vapor deposition equipment is a stainless steel reaction chamber.

[0057] The materials and reagents used are as follows: high-purity graphite blank (30mm*40mm*50mm), high-purity methane (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), and high-purity tantalum ethoxide (99.99%). The implementation steps are as follows:

[0058] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500 Pa and maintained at a vacuum state of 500 Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed, argon is introduced to fill the equipment to a normal pressure state, so that the argon fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0059] (2) After cleaning the high-purity graphite blank with distilled water and drying it at 170°C for 8 hours, place it in the reaction chamber, ensuring that the surface of the blank to be deposited faces the outlet of the reaction gas and that the blanks do not overlap or block each other;

[0060] (3) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 15 minutes. After checking that the vapor deposition equipment is sealed, introduce argon gas to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the air valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0061] (4) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 10 minutes. After checking that the vapor deposition equipment is sealed intact, control the vacuum degree in the vapor deposition equipment to 500 Pa through a vacuum pump, and heat the temperature in the reaction chamber to 500°C.

[0062] (5) placing tantalum ethoxide in a vaporization chamber and heating it to 200° C. to vaporize it, and introducing the vaporized tantalum ethoxide gas into a gas mixing tank. At the same time, introducing hydrogen and methane gas into the gas mixing tank. The ratio of tantalum ethoxide, methane, and hydrogen is 1:1:1, and the flow rates are 2 SLM, 2 SLM, and 2 SLM, respectively. After being fully mixed in the gas mixing tank, the mixture is introduced into a reaction chamber to carry out a chemical vapor deposition reaction on the blank for 3 hours to prepare a tantalum carbide coated graphite material.

[0063] (6) Disconnect the heating power supply and allow the reaction chamber to cool naturally. When the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon. After the reaction chamber is filled to normal pressure, stop introducing argon, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coated graphite material.

[0064] The thickness of the tantalum carbide coating on the prepared tantalum carbide-coated graphite material was measured using an electron microscope, and the test results showed that the coating thickness was 23μm. The adhesion of the tantalum carbide coating on the prepared tantalum carbide-coated graphite material was tested according to the ISO 4624-2016 coating adhesion test standard. The peel strength of the tantalum carbide coating on the prepared tantalum carbide-coated graphite material was tested and the test showed 23MPa. The graphite substrate was pulled apart, and the coating did not detach. Figure 2 This is a cross-sectional view of the tantalum carbide coating in Example 1. Figure 5 This is the surface morphology of the tantalum carbide coating of Example 1. Figure 7 The metallographic images show no cracking. X-ray photoelectron spectroscopy (XPS) analysis of the tantalum carbide coating revealed no other elements besides Ta, C, and O. Oxygen, which is absorbed by the sample from the atmosphere and carbon dioxide, is difficult to remove during XPS analysis.

[0065] Example 2

[0066] The chemical vapor deposition equipment is a stainless steel reaction chamber.

[0067] The materials and reagents used are as follows: high-purity graphite blank (100mm*50mm*20mm), high-purity methane (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), and high-purity tantalum ethoxide (99.99%). The implementation steps are as follows:

[0068] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500 Pa and maintained at a vacuum state of 500 Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed, argon is introduced to fill the equipment to a normal pressure state, so that the argon fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0069] (2) After cleaning the high-purity graphite blank with distilled water and drying it at 150°C for 8 hours, place it in the reaction chamber, ensuring that the surface to be deposited faces the outlet of the reaction gas and that the blanks do not overlap or block each other;

[0070] (3) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 15 minutes. After checking that the vapor deposition equipment is sealed, introduce argon gas to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the air valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0071] (4) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 10 minutes. After checking that the vapor deposition equipment is sealed, control the vacuum degree in the vapor deposition equipment to 1000 Pa through a vacuum pump, and heat the temperature in the reaction chamber to 450°C.

[0072] (5) placing tantalum ethanol in a vaporization chamber and heating it to 200° C. to vaporize it, and introducing the vaporized tantalum ethanol gas into a gas mixing tank. At the same time, introducing hydrogen and methane gas into the gas mixing tank. The ratio of tantalum ethanol, methane, and hydrogen is 1:1:1, and the flow rates are 2 SLM, 2 SLM, and 2 SLM, respectively. After being fully mixed in the gas mixing tank, the gas is introduced into a reaction chamber to carry out a chemical vapor deposition reaction on the blank for 10 hours to prepare a tantalum carbide coated graphite material.

[0073] (6) Disconnect the heating power supply and allow the reaction chamber to cool naturally. When the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon. After the reaction chamber is filled to normal pressure, stop introducing argon, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide-coated graphite carbon material.

[0074] The thickness of the tantalum carbide coating on the prepared tantalum carbide coated graphite material was detected using an electron microscope, and the detection results showed that the coating thickness was 75 μm. Figure 3-Figure 4 This is a cross-sectional view of the tantalum carbide coating in Example 2. Figure 6 This is the surface morphology of the tantalum carbide coating from Example 2, showing no cracking. X-ray photoelectron spectroscopy (XPS) analysis of the tantalum carbide coating revealed no other elements besides Ta, C, and O. Oxygen, which is absorbed by the sample from the atmosphere and carbon dioxide, is difficult to remove during XPS analysis.

[0075] Example 3

[0076] The chemical vapor deposition equipment is a stainless steel reaction chamber.

[0077] The materials and reagents used are as follows: high-purity graphite blank (30mm*30mm*30mm), high-purity methane (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), and high-purity tantalum ethoxide (99.99%). The implementation steps are as follows:

[0078] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500 Pa and maintained at a vacuum state of 500 Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed, argon is introduced to fill the equipment to a normal pressure state, so that the argon fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0079] (2) After the high-purity green body is cleaned with distilled water and dried at 150°C for 8 hours, it is placed in the reaction chamber, ensuring that the surface of the green body to be deposited faces the direction of the reaction gas outlet and that the green bodies do not overlap or block each other;

[0080] (3) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 15 minutes. After checking that the vapor deposition equipment is sealed, introduce argon gas to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the air valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0081] (4) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 10 minutes. After checking that the vapor deposition equipment is sealed, control the vacuum degree in the vapor deposition equipment to 15000 Pa by using a vacuum pump, and heat the temperature in the reaction chamber to 400 ° C.

[0082] (5) placing tantalum ethoxide in a vaporization chamber and heating it to 200° C. to vaporize it, and introducing the vaporized tantalum ethoxide gas into a gas mixing tank. At the same time, introducing hydrogen and methane gas into the gas mixing tank. The ratio of tantalum ethoxide, methane, and hydrogen is 1:1:2, and the flow rates are 2 SLM, 2 SLM, and 4 SLM, respectively. After being fully mixed in the gas mixing tank, the gas is introduced into a reaction chamber to carry out a chemical vapor deposition reaction on the blank for 10 hours to prepare a tantalum carbide coated graphite material.

[0083] (6) Disconnect the heating power supply and allow the reaction chamber to cool naturally. When the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon. After the reaction chamber is filled to normal pressure, stop introducing argon, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coated graphite material.

[0084] The thickness of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested using an electron microscope, and the test results showed that the coating thickness was 80μm. According to the ISO 4624-2016 coating adhesion test standard, the adhesion of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested. The peel strength was 22MPa, the graphite substrate was pulled apart, and the coating did not detach. The surface morphology of the coating was observed using a scanning electron microscope and no cracking was found. The tantalum carbide coating was analyzed by X-ray photoelectron spectroscopy (XPS), and it was determined that there were no other elements except Ta, C, and O. The oxygen element comes from the oxygen and carbon dioxide adsorbed by the sample in the atmosphere, and it is difficult to remove in the XPS test.

[0085] Example 4

[0086] The chemical vapor deposition equipment is a stainless steel reaction chamber.

[0087] The materials and reagents used are as follows: high-purity carbon / carbon blank (30mm*30mm*30mm), high-purity methane (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), and high-purity tantalum ethoxide (99.99%). The implementation steps are as follows:

[0088] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500 Pa and maintained at a vacuum state of 500 Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed, argon is introduced to fill the equipment to a normal pressure state, so that the argon fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0089] (2) After cleaning the high-purity carbon / carbon blank with distilled water and drying it at 150°C for 8 hours, place it in the reaction chamber, ensuring that the surface to be deposited faces the outlet of the reaction gas and that the blanks do not overlap or block each other;

[0090] (3) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 15 minutes. After checking that the vapor deposition equipment is sealed, introduce argon gas to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the air valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0091] (4) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 10 minutes. After checking that the vapor deposition equipment is sealed, control the vacuum degree in the vapor deposition equipment to 15000 Pa by using a vacuum pump, and heat the temperature in the reaction chamber to 400 ° C.

[0092] (5) placing tantalum ethanol in a vaporization chamber and heating it to 200° C. to vaporize it, and introducing the vaporized tantalum ethanol gas into a gas mixing tank. At the same time, introducing hydrogen and methane gas into the gas mixing tank. The ratio of tantalum ethanol, methane, and hydrogen is 1:1:2, and the flow rates are 2 SLM, 2 SLM, and 4 SLM, respectively. After being fully mixed in the gas mixing tank, the gas is introduced into a reaction chamber to carry out a chemical vapor deposition reaction on the blank for 10 hours to prepare a tantalum carbide coated carbon / carbon material.

[0093] (6) Disconnect the heating power supply and allow the reaction chamber to cool naturally. When the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon. After the reaction chamber is filled to normal pressure, stop introducing argon, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coated carbon / carbon material.

[0094] The thickness of the tantalum carbide coating of the prepared tantalum carbide coated carbon / carbon material was tested using an electron microscope, and the test results showed that the coating thickness was 78μm. According to the ISO 4624-2016 coating adhesion test standard, the adhesion of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested. The peel strength was tested to be 127MPa. The upper surface of the carbon / carbon substrate was peeled off, and the coating did not detach. The surface morphology of the coating was observed using a scanning electron microscope and no cracking was found. The tantalum carbide coating was analyzed by X-ray photoelectron spectroscopy (XPS), and it was determined that there were no other elements except Ta, C, and O. The oxygen element comes from the oxygen and carbon dioxide adsorbed by the sample in the atmosphere, and it is difficult to remove in the XPS test.

[0095] Example 5

[0096] The chemical vapor deposition equipment is a stainless steel reaction chamber.

[0097] The materials and reagents used are as follows: high-purity graphite blank (30mm*30mm*30mm), high-purity methane (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), and high-purity tantalum ethoxide (99.99%). The implementation steps are as follows:

[0098] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500 Pa and maintained at a vacuum state of 500 Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed, argon is introduced to fill the equipment to a normal pressure state, so that the argon fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0099] (2) After the high-purity green body is cleaned with distilled water and dried at 150°C for 8 hours, it is placed in the reaction chamber, ensuring that the surface of the green body to be deposited faces the direction of the reaction gas outlet and that the green bodies do not overlap or block each other;

[0100] (3) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 15 minutes. After checking that the vapor deposition equipment is sealed, introduce argon gas to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the air valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0101] (4) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 10 minutes. After checking that the vapor deposition equipment is sealed, control the vacuum degree in the vapor deposition equipment to 15000 Pa by using a vacuum pump, and heat the temperature in the reaction chamber to 400 ° C.

[0102] (5) placing tantalum ethanol in a vaporization chamber and heating it to 200°C to vaporize it, and introducing the vaporized tantalum ethanol gas into a gas mixing tank. At the same time, introducing hydrogen and methane gas into the gas mixing tank. The ratio of tantalum ethanol, methane, and hydrogen is 1:2:3, and the flow rates are 6 SLM, 12 SLM, and 18 SLM, respectively. After being fully mixed in the gas mixing tank, the gas is introduced into a reaction chamber to perform a chemical vapor deposition reaction on the blank for 2 hours to prepare a tantalum carbide coated graphite material.

[0103] (6) Disconnect the heating power supply and allow the reaction chamber to cool naturally. When the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon. After the reaction chamber is filled to normal pressure, stop introducing argon, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coated graphite material.

[0104] The thickness of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested using an electron microscope, and the test results showed that the coating thickness was 58μm. According to the ISO 4624-2016 coating adhesion test standard, the adhesion of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested. The peel strength was tested to be 24MPa, the graphite substrate was pulled apart, and the coating did not detach. The surface morphology of the coating was observed using a scanning electron microscope and no cracking was found. The tantalum carbide coating was analyzed by X-ray photoelectron spectroscopy (XPS), and it was determined that there were no other elements except Ta, C, and O. The oxygen element comes from the oxygen and carbon dioxide adsorbed by the sample in the atmosphere, and it is difficult to remove in the XPS test.

[0105] Example 6

[0106] The chemical vapor deposition equipment is a stainless steel reaction chamber.

[0107] The materials and reagents used are as follows: high-purity graphite blank (30mm*30mm*30mm), high-purity methane (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), and high-purity tantalum ethoxide (99.99%). The implementation steps are as follows:

[0108] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500 Pa and maintained at a vacuum state of 500 Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed, argon is introduced to fill the equipment to a normal pressure state, so that the argon fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0109] (2) After the high-purity green body is cleaned with distilled water and dried at 150°C for 8 hours, it is placed in the reaction chamber, ensuring that the surface of the green body to be deposited faces the direction of the reaction gas outlet and that the green bodies do not overlap or block each other;

[0110] (3) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 15 minutes. After checking that the vapor deposition equipment is sealed, introduce argon gas to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the air valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0111] (4) Evacuate to a vacuum state of 1000 Pa and maintain the vacuum state of 1000 Pa for 10 minutes. After checking that the vapor deposition equipment is sealed, control the vacuum degree in the vapor deposition equipment to 20000 Pa by using a vacuum pump, and heat the temperature in the reaction chamber to 500 ° C.

[0112] (5) placing tantalum ethanol in a vaporization chamber and heating it to 300°C to vaporize it, and introducing the vaporized tantalum ethanol gas into a gas mixing tank. At the same time, introducing hydrogen and methane into the gas mixing tank. The ratio of tantalum ethanol, methane, and hydrogen is 1:2:3, and the flow rates are 2SLM, 4SLM, and 6SLM, respectively. After being fully mixed in the gas mixing tank, the gas is introduced into a reaction chamber to carry out a chemical vapor deposition reaction on the blank for 8 hours to prepare a tantalum carbide coated graphite material.

[0113] (6) Disconnect the heating power supply and allow the reaction chamber to cool naturally. When the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon. After the reaction chamber is filled to normal pressure, stop introducing argon, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coated graphite material.

[0114] The thickness of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested using an electron microscope, and the test results showed that the coating thickness was 51μm. According to the ISO 4624-2016 coating adhesion test standard, the adhesion of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested. The peel strength was 23MPa, the graphite substrate was pulled apart, and the coating did not detach. The surface morphology of the coating was observed using a scanning electron microscope and no cracking was found. The tantalum carbide coating was analyzed by X-ray photoelectron spectroscopy (XPS), and it was determined that there were no other elements except Ta, C, and O. The oxygen element comes from the oxygen and carbon dioxide adsorbed by the sample in the atmosphere, and it is difficult to remove in the XPS test.

[0115] The above embodiments and figures do not limit the product form and style of the present invention. Any appropriate changes or modifications made by ordinary technicians in the relevant technical field, such as changes in parameters such as reaction temperature, vaporization temperature, and gas flow rate, should be deemed to be within the scope of the patent of the present invention.

Claims

1. A method for preparing a tantalum carbide coating by CVD, characterized in that: Tantalum alkoxide is used as a precursor, and after being gasified, it is subjected to a reduction reaction with alkanes and hydrogen in a chemical vapor deposition device, and deposited on the surface of the blank to prepare the desired tantalum carbide coating; the tantalum alkoxide is at least one of tantalum methanol or tantalum ethoxide; The following steps are involved: (1) a heating step, placing the substrate in a CVD reaction chamber, evacuating the reaction chamber, and heating under the protection of an inert gas, wherein the heating temperature is 400 to 500° C.; (2) a deposition step, after the heating step, introducing a mixture of tantalum alkoxide gas, alkane, and hydrogen into the reaction chamber, heating the chamber at a pressure of 15000 Pa to 20000 Pa while maintaining the temperature at 400 to 500° C., to deposit a tantalum carbide coating on the surface of the substrate; (3) a cooling step, after the deposition step, cooling the tantalum carbide coating product to room temperature; Wherein, in step (2), the volume ratio of the tantalum alkoxide gas to the alkane is 1:1-2, and the volume ratio of the tantalum alkoxide gas to hydrogen is 1:1-3.

2. The method for preparing a tantalum carbide coating by CVD according to claim 1, characterized in that: The alkane is at least one of methane, ethane and propane.

3. The method for preparing a tantalum carbide coating by CVD according to claim 1, characterized in that: The gasification temperature of the tantalum alkoxide is 200-300°C.

4. The method for preparing a tantalum carbide coating by CVD according to claim 1, characterized in that: The reaction chamber is a stainless steel reaction chamber.

5. The method for preparing a tantalum carbide coating by CVD according to claim 1, characterized in that: The flow rate of the tantalum alkoxide gas is 2-6 SLM, the flow rate of the alkane gas is 2-12 SLM, and the flow rate of the hydrogen gas is 2-18 SLM.

6. The method for preparing a tantalum carbide coating by CVD according to claim 1, characterized in that: The heating step also includes pretreatment of the substrate: the surface of the substrate to be deposited is cleaned with distilled water to remove dirt, and then dried at 150° C. to 200° C. for 8 to 15 hours until it is completely dried.

7. A product having a tantalum carbide coating prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The invention comprises a substrate and a tantalum carbide coating formed on the surface of the substrate, wherein the thickness of the tantalum carbide coating is 15 to 300 microns.

8. The product having a tantalum carbide coating according to claim 7, characterized in that: The substrate includes at least one of metal, carbon material, ceramic and quartz.

Citation Information

Patent Citations

  • Tantalum carbide coating carbon material and preparation method thereof

    CN114572975A